Bird responses to forest loss are influence by habitat specialization - Zurita, Gustavo Andrés (2017)
Fil: Zurita, Gustavo Andrés. Consejo Nacional de Investigaciones Científicas y Técnicas. Facultad de Ciencias Forestales. Instituto de Biología Subtropical; Argentina.